Suppression of tumorigenicity‐2 (ST2) is a promising biomarker in heart transplantation. Issue 5 (22nd February 2022) - Galeone, Antonella; Salem, Joe‐Elie; Lebreton, Guillaume; Coutance, Guillaume; Nguyen, Lee; Hulot, Jean Sébastien; Atassi, Fabrice; Bega, Marco; Leprince, Pascal; Varnous, Shaida
Abstract: Background: To evaluate the association between donors' and recipients' serum levels of soluble ST2 (sST2) and recipients' outcome after heart transplantation (HT). Methods: Blood samples were collected in 50 heart donors before organ procurement and in 50 recipients before HT (D0), a week after HT (D7) and at every first year's endomyocardial biopsy (EMB); sST2 levels were evaluated by ELISA. Results: Donors who sustained a cardiac arrest, had significantly higher sST2 levels. Recipients on national high emergency waiting list had significantly higher preoperative sST2 levels compared to recipients who did not. Recipients with postoperative sepsis or continuous renal replacement therapy had significantly higher sST2 levels at D7. Recipients who needed a postoperative ECMO for allograft dysfunction had significantly higher sST2 levels in their corresponding donors. Recipients who died during the hospitalization after the transplantation had significantly higher sST2 levels at D7 compared to recipients who did not. No difference was observed in sST2 levels in recipients who had mild allograft rejection and recipient who did not. Conclusions: Higher sST2 levels in donors are associated to allograft dysfunction requiring ECMO in recipients; higher postoperative sST2 levels in recipients are associated with in‐hospital mortality.